HUBUNGAN PENGETAHUAN KOSMETIK DENGAN PEMILIHAN KOSMETIK PERAWATAN RAMBUT PADA ANGGOTA LPKK DI DUKUH MOJOSAWIT KLATEN - Tri Fatmawati (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This study aimed to know (1) hair cosmetic knowledge, and (2) hair care cosmetic choice, and (3) correlation between hair cosmetic knowledge and hair care cosmetic choice. The type of this study was ex-post facto. Data collection techniques used questionnaires and documentation. Data analysis techniques used a descriptive analysis and hypothesis testing used Product Moment that was started by normality and linearity test. This study shows that hair cosmetic knowledge was in high category with the relative frequency 39.51% and hair care cosmetic choice was in high category with the relative frequency 64.20%. The score of rxy was 0.408 above rtable = 0.220 (rxy = 0.408 > rtable 0.220). It means that there was a positive and significant correlation between hair cosmetic knowledge and hair care cosmetic choice. The score of determinant coefficient (R2) was 0.167, it means that hair cosmetic knowledge gave a positive contribution 16.7% toward hair care cosmetic choice, while 83.3% was influenced by other factors that were not analyzed in this research.Â Key words: cosmetic knowledge, hair care cosmetic choiceÂ